Manufacturing method of reflective electrode for deep ultraviolet light emitting device, and manufacturing method of deep ultraviolet light emitting device
A super-lattice structured reflective electrode using nickel and rhodium for the P-type contact layer in deep-ultraviolet light elements addresses the reliability issues of high AL composition ratios, maintaining high emission output and preventing sudden failures.
Patent Information
- Application Number
- JP2020090012
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-22
- Filing Date
- 2020-05-22
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2040-01-17
AI Technical Summary
Existing deep-ultraviolet light elements face issues with high light emission output being compromised by sudden decreases or failures in reliability due to increased permeability of the P-type contact layer, particularly when the AL composition ratio is elevated.
A method involving a super-lattice structure for the P-type contact layer, where nickel (Ni) and rhodium (Rh) are used as metal layers with specific thicknesses and subjected to heat treatment, forming a reflective electrode that balances high light emission and reliability.
The method achieves a reflective electrode that maintains high light emission output while ensuring excellent reliability by optimizing the AL composition ratio and layer structure, preventing sudden failures.
Smart Images

Figure 0007623794000009 
Figure 0007623794000010 
Figure 0007623794000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a reflective electrode for a deep ultraviolet light-emitting element, a method for manufacturing a deep ultraviolet light-emitting element, and a deep ultraviolet light-emitting element, and in particular to a method for manufacturing a reflective electrode for a deep ultraviolet light-emitting element that can achieve both high light emission output and excellent reliability. [Background technology]
[0002] Group III nitride semiconductors, which consist of compounds of N with Al, Ga, In, etc., are wide band gap semiconductors with a direct transition band structure, and are materials expected to be used in a wide range of applications such as sterilization, water purification, medicine, lighting, high-density optical recording, etc. In particular, light-emitting devices that use group III nitride semiconductors in the light-emitting layer can cover the deep ultraviolet to visible light range by adjusting the content ratio of group III elements, and efforts are being made to put them into practical use in various light sources.
[0003] Light with a wavelength of 200 to 350 nm is called deep ultraviolet light, and deep ultraviolet light-emitting devices that emit deep ultraviolet light are generally fabricated as follows. That is, a buffer layer is formed on a substrate such as sapphire or AlN single crystal, and an n-type semiconductor layer, a light-emitting layer, and a p-type semiconductor layer made of a group III nitride semiconductor are sequentially formed. Next, an n-side electrode that is electrically connected to the n-type semiconductor layer and a p-side electrode that is electrically connected to the p-type semiconductor layer are formed. Here, it has been common to form a p-type GaN contact layer that is easy to increase the hole concentration on the p-side electrode side of the p-type semiconductor layer in order to make an ohmic contact. Note that a multiple quantum well (MQW) structure in which barrier layers and well layers made of group III nitride semiconductors are alternately stacked is widely used for the light-emitting layer.
[0004] One of the characteristics required for deep ultraviolet light-emitting devices is high external quantum efficiency, which is determined by (i) internal quantum efficiency, (ii) electron inflow efficiency, and (iii) light extraction efficiency.
[0005] Patent Document 1 discloses a deep ultraviolet light-emitting diode that includes a p-type contact layer of AlGaN mixed crystal and a p-side reflecting electrode that is reflective to the light emitted from the light-emitting layer, and has the substrate side as the light extraction direction. For short-wavelength light, the higher the Al composition ratio of the p-type contact layer made of AlGaN, the higher the transmittance of the p-type contact layer can be. Therefore, Patent Document 1 proposes using a p-type contact layer made of AlGaN that has a transmittance according to the emission wavelength, instead of the conventional p-type contact layer made of GaN. In addition, it is preferable that the reflecting electrode in this case be a metal film mainly composed of Al. Ni is used as the insertion metal layer for ohmic contact.
[0006] In Patent Document 2, taking into consideration that metals such as nickel (Ni) and cobalt (Co) have a small amount of reflection of visible light having a wavelength of 380 nm to 550 nm (blue-violet, blue, green), the Patent Document 2 discloses a Group III nitride semiconductor light-emitting device that uses silver (Ag), rhodium (Rh), ruthenium (Ru), platinum (Pt) or palladium (Pd) for a positive electrode on a p-type semiconductor layer (e.g., a p-type GaN layer) and has a first thin-film metal layer having a thickness of 0.2 to 20 nm and made of cobalt (Co) or nickel (Ni) between the positive electrode on the p-type semiconductor layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2015-216352 A [Patent Document 2] JP 2000-36619 A Summary of the Invention [Problem to be solved by the invention]
[0008] According to Patent Document 1, the higher the transmittance of the p-type contact layer for emitted light, the more preferable it is. Therefore, according to Patent Document 1, the higher the Al composition ratio of the p-type contact layer, the more preferable it is.
[0009] However, according to the experiments of the present inventors, it has been found that simply increasing the Al composition ratio of the p-type contact layer in contact with the p-side electrode to increase the transmittance of the central emission wavelength of the emitted deep ultraviolet light is not practical for the following reasons. First, it is certainly possible to obtain a deep ultraviolet light-emitting device with a higher emission output than the conventional technology by increasing the transmittance of the deep ultraviolet light in the p-type contact layer. However, when an overload reliability test (specifically, a current of 100 mA for 3 seconds) was performed on a sample of the deep ultraviolet light-emitting device thus fabricated, a phenomenon was confirmed in some of the samples in which the emission output suddenly decreased to half of the initial emission output, or the device suddenly stopped lighting (hereinafter also referred to as "sudden death").
[0010] The inventors also conducted research into the relationship between the type of electrode used in deep-ultraviolet light-emitting diodes and the Al composition ratio of the p-type contact layer. When rhodium (Rh), which has a relatively high reflectivity in the ultraviolet range but is inferior to aluminum (Al) as a reflective electrode, is used when formed on a p-type GaN layer, it can be used as an electrode. However, when it is formed on a single-layer p-type AlGaN layer with an Al composition of 30% or more, the sudden death described above is confirmed, and it is found that the electrode cannot be reliable.
[0011] An element whose light emission output suddenly deteriorates in this way has insufficient reliability, and it is not acceptable in terms of product quality control for an element with insufficient reliability to be mixed into a product. Therefore, an object of the present invention is to provide a method for manufacturing a reflective electrode for a deep ultraviolet light-emitting element that can achieve both high light emission output and excellent reliability. Another object of the present invention is to provide a method for manufacturing a deep ultraviolet light-emitting element using the reflective electrode, and a deep ultraviolet light-emitting element obtained thereby. [Means for solving the problem]
[0012] The present inventors have intensively studied ways to solve the above problems. They have experimentally confirmed that when rhodium (Rh), which has a relatively high reflectance in the ultraviolet region, is used as the metal material for the reflective electrode, the above problems can be solved by providing a metal layer made of nickel (Ni) between rhodium and the p-type contact layer of the superlattice structure, and have completed the present invention. That is, the gist of the present invention is as follows.
[0013] (1) On a p-type contact layer having a superlattice structure, A first step of forming a first metal layer of Ni to a thickness of 3 to 20 nm; a second step of forming a second metal layer of Rh on the first metal layer to a thickness of 20 nm or more and 2 μm or less; a third step of subjecting the first metal layer and the second metal layer to a heat treatment at a temperature of 300° C. or more and 600° C. or less; A method for manufacturing a reflective electrode for a deep ultraviolet light-emitting element, comprising:
[0014] (2) The method for producing a reflective electrode for a deep ultraviolet light-emitting device according to (1) above, wherein the atmospheric gas used for the heat treatment in the third step contains oxygen.
[0015] (3) The method for producing a reflective electrode for a deep ultraviolet light-emitting element according to (1) or (2) above, further comprising the step of forming a Ni layer as a third metal layer on the second metal layer after the second step, wherein the reflective electrode is formed only from Ni and Rh.
[0016] (4) forming an n-type semiconductor layer on the substrate; forming a light emitting layer on the n-type semiconductor layer; forming a p-type electron blocking layer on the light emitting layer; forming a p-type contact layer on the p-type electron blocking layer; forming a reflective electrode on the p-type contact layer; A method for producing a deep ultraviolet light emitting device comprising: The step of forming the p-type contact layer includes forming an Al x Ga1-x A first step of forming a first layer made of N and a second step of forming an Al layer having an Al composition ratio y lower than the Al composition ratio x. y Ga 1-y and a second step of forming a second layer made of N, the p-type contact layer having a superlattice structure is formed by alternately repeating these steps, and an Al composition ratio y of the second layer is 0.15 or more, The step of forming a reflective electrode includes: On the second layer on the outermost surface of the p-type contact layer, A first step of forming a first metal layer of Ni to a thickness of 3 to 20 nm; a second step of forming a second metal layer of Rh on the first metal layer to a thickness of 20 nm or more and 2 μm or less; a third step of performing a heat treatment on the first metal layer and the second metal layer at 300 to 600° C.; A method for manufacturing a deep ultraviolet light-emitting device, comprising:
[0017] (5) In the superlattice structure of the p-type contact layer, When the Al composition ratio of the layer that emits deep ultraviolet light in the light emitting layer is w0, the Al composition ratio x of the first layer is higher than the Al composition ratio w0, the Al composition ratio y of the second layer is lower than the Al composition ratio x, The Al composition ratio w0, the Al composition ratio x, the Al composition ratio y, and the thickness-average Al composition ratio z of the p-type contact layer are expressed by the following formulas [1] and [2]: 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2] The method for producing a deep ultraviolet light-emitting device according to the above (4), which satisfies the above.
[0018] (6) The method for producing a deep ultraviolet light-emitting device according to the above (5), further comprising a guide layer between the p-type electron blocking layer and a well layer in the light-emitting layer that is closest to the p-type electron blocking layer, the guide layer having an Al composition ratio higher than the Al composition ratio of either of the barrier layer of the light-emitting layer and the p-type electron blocking layer.
[0019] (7) The method for producing a deep ultraviolet light-emitting device according to (6) above, wherein the guide layer is made of AlN.
[0020] (8) The method for producing a deep ultraviolet light-emitting device according to any one of (5) to (7) above, wherein the Al composition ratio w0 is 0.25 or more and 0.60 or less.
[0021] (9) The method for producing a deep ultraviolet light-emitting device according to any one of the above (4) to (8), wherein the total thickness of the p-type layers, that is, the p-type electron blocking layer and the p-type contact layer, is 65 to 100 nm.
[0022] (10) The method for producing a deep ultraviolet light-emitting device according to any one of (4) to (9) above, further comprising the step of forming a Ni layer as a third metal layer on the second metal layer after the second step, and the reflective electrode is formed of only Ni and Rh.
[0023] (11) An n-type semiconductor layer, a light emitting layer, a p-type electron blocking layer, and a p-type contact layer are sequentially formed on a substrate; The p-type contact layer has an Al composition ratio x. x Ga 1-x The first layer is made of N and the second layer is made of Al having an Al composition ratio y. y Ga 1-y and a second layer made of N, and the Al composition ratio y of the second layer is 0.15 or more; A deep ultraviolet light emitting device comprising a reflective electrode made of Ni and Rh on the second layer, which is the outermost surface of the p-type contact layer.
[0024] (12) In the superlattice structure of the p-type contact layer, When the Al composition ratio of the layer that emits deep ultraviolet light in the light emitting layer is w0, the Al composition ratio x of the first layer is higher than the Al composition ratio w0, the Al composition ratio y of the second layer is lower than the Al composition ratio x, The Al composition ratio w0, the Al composition ratio x, the Al composition ratio y, and the thickness-average Al composition ratio z of the p-type contact layer are expressed by the following formulas [1] and [2]: 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2] The deep ultraviolet light-emitting device according to the above (11), which satisfies the above.
[0025] The deep ultraviolet light emitting device according to the above (11) or (12), wherein the total thickness of the p-type layers, that is, the p-type electron blocking layer and the p-type contact layer, is 65 to 100 nm. Effect of the Invention
[0026] According to the present invention, it is possible to provide a method for producing a reflective electrode for a deep ultraviolet light-emitting device that can achieve both high light emission output and excellent reliability. Furthermore, the present invention can provide a method for producing a deep ultraviolet light-emitting device using the reflective electrode, and a deep ultraviolet light-emitting device obtained thereby. [Brief description of the drawings]
[0027] [Figure 1A] 2A to 2C are schematic cross-sectional views illustrating a process for manufacturing a reflective electrode for a deep ultraviolet light-emitting device according to an embodiment of the present invention. [Figure 1B] 5A to 5C are schematic cross-sectional views illustrating a process for manufacturing a reflective electrode for a deep ultraviolet light emitting device according to another embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view illustrating a deep ultraviolet light-emitting device according to one embodiment of the present invention. [Diagram 3] 2A to 2C are schematic cross-sectional views illustrating a process for manufacturing a deep ultraviolet light-emitting device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Prior to describing the embodiments according to the present invention, the following points will be explained in advance. First, in this specification, when the term "AlGaN" is used without specifying the Al composition ratio, it means an arbitrary compound in which the composition ratio of group III elements (total of Al and Ga) to N is 1:1, and the ratio of group III elements Al to Ga is indefinite. Furthermore, even if "AlGaN" does not specify In, which is a group III element, it may contain up to 5% In relative to the total of Al and Ga as group III elements, and a composition formula containing In is written as Al, with the Al composition ratio being x0 and the In composition ratio being y0 (0≦y0≦0.05). x0 In y0 Ga 1-x0-y0 N. When simply written as "AlN" or "GaN", it means that Ga and Al are not included, respectively, but unless otherwise specified, simply writing "AlGaN" does not exclude either AlN or GaN. The value of the Al composition ratio can be measured by photoluminescence measurement, X-ray diffraction measurement, etc.
[0029] In this specification, a layer that functions electrically as p-type is referred to as a p-type layer, and a layer that functions electrically as n-type is referred to as an n-type layer. On the other hand, a layer that does not function electrically as p-type or n-type because specific impurities such as Mg or Si are not intentionally added is called an "i-type" or "undoped" layer. An undoped layer may contain unavoidable impurities during the manufacturing process, and specifically, a layer with a small carrier density (e.g., 4×10 16 / cm 3 In this specification, when the impurity concentration is less than 100%, the impurity concentration is referred to as "undoped." The impurity concentration values of Mg, Si, etc. are based on SIMS analysis.
[0030] The overall thickness of each layer formed by epitaxial growth can be measured using an optical interference film thickness measuring device. Furthermore, when the composition of each adjacent layer is sufficiently different (for example, when the Al composition ratio differs by 0.01 or more), the thickness of each layer can be calculated from a cross-sectional observation of the grown layer using a transmission electron microscope. Furthermore, for adjacent layers that have the same or nearly the same Al composition ratio (for example, less than 0.01) but different impurity concentrations, the boundary between the two layers and the thickness of each layer are measured based on TEM-EDS. The impurity concentrations of both layers can be measured by SIMS analysis. Furthermore, when the thickness of each layer is thin, such as in a superlattice structure, the thickness can be measured using TEM-EDS.
[0031] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In principle, the same components are given the same reference numerals and the description will be omitted. In addition, in each drawing, the aspect ratio of the substrate and each layer is exaggerated from the actual ratio for the convenience of explanation.
[0032] (Reflecting electrode) FIG. 1A shows a p-side reflective electrode 80 obtained by a method for manufacturing a reflective electrode for a deep ultraviolet light-emitting device according to one embodiment of the present invention. FIG. 2 is a schematic cross-sectional view of a deep ultraviolet light-emitting device 100 having the reflective electrode 80. In the following, the symbols in FIG. 1A and FIG. 2 will be referred to. The reflective electrode 80 can be provided directly on the p-type contact layer 70. The reflective electrode 80 is a reflective electrode using a metal having a high reflectance (for example, 60% or more) to the ultraviolet light emitted from the light-emitting layer 40, and in the present invention, rhodium (Rh) is used as a metal having such a reflectance (hereinafter referred to as a "reflective metal"). For rhodium (Rh), for example, commercially available metal rhodium (for example, 3N purity) can be used as a deposition source. The p-type contact layer 70 has a superlattice structure, and the p-side reflective electrode obtained by forming the reflective metal on the p-type contact layer 70 through nickel (Ni) to a certain thickness or more has a high reflectance to deep ultraviolet light. Furthermore, it was found that a relatively good ohmic contact can be made between the p-type contact layer 70 and the p-side reflective electrode 80 by performing a heat treatment at 300° C. or more and 600° C. or less, and that the reliability is sufficient to withstand a high current. Since it is extremely difficult to directly measure the reflectance of the reflective electrode 80 in the state of the deep-ultraviolet light-emitting device 100, the reflectance is measured by forming the first metal layer 81 and the second metal layer 82 on a sapphire substrate, applying light of each wavelength from the transparent sapphire substrate side to the reflective electrode 80 before and after the heat treatment process, and measuring the reflectance for the wavelength (for example, the reflectance for a wavelength of 300 nm) using an ultraviolet-visible spectrophotometer.
[0033] That is, as shown in FIG. 1A, a method for manufacturing a reflective electrode for a deep-ultraviolet light-emitting device according to one embodiment of the present invention includes a first step (FIG. 1A, step 1B) of forming Ni as a first metal layer 81 to a thickness of 3 to 20 nm on a p-type contact layer 70 having a superlattice structure (FIG. 1A, step 1A), a second step (FIG. 1A, step 1C) of forming Rh as a second metal layer 82 to a thickness of 20 nm or more and 2 μm or less on the first metal layer 81, and a third step (FIG. 1A, step 1D) of performing a heat treatment at a temperature of 300° C. or more and 600° C. or less on the first metal layer and the second metal layer.
[0034] <1st process> In the first step, Ni is formed as the first metal layer 81 on the p-type contact layer 70 to a thickness of 3 to 20 nm. Ni can be deposited on the surface of the p-type contact layer 70 by a general method such as a vacuum deposition method such as an electron beam deposition method and a resistance heating deposition method, and a sputtering method. If the thickness is less than 3 nm, it becomes difficult to suppress the sudden death described above, and if the thickness exceeds 20 nm, the reflectance of the reflective electrode decreases significantly. It is more preferable that the thickness of the first metal layer 81 is 3 to 10 nm. By forming the first metal layer 81 to a thickness of 10 nm or less, the reflectance of the reflective electrode 80 after the heat treatment can be 60% or more for a wavelength of 300 nm. The thickness of the first metal layer 81 can be measured using a quartz crystal film thickness meter.
[0035] <Second process> In the second step, Rh is formed as the second metal layer 82 on the first metal layer 81 to a thickness of 20 nm to 2 μm. If the thickness is less than 20 nm, the reflectance of the second metal layer 82 to ultraviolet light may not be sufficiently high. If the thickness exceeds 2 μm, the cost of Rh may be a problem. In order to improve the reflectance of the reflective electrode after the first metal layer 81 is diffused by the heat treatment step described later, the thickness of the second metal layer 82 is more preferably 30 nm or more, and more preferably 100 nm or less to reduce costs. In the second step, the second metal layer can be formed by a general method such as a vacuum deposition method or a sputtering method, as in the first step. The thickness of the second metal layer 82 can be measured using a quartz crystal film thickness gauge.
[0036] <3rd process> In the third step, the first metal layer 81 and the second metal layer 82 are subjected to a heat treatment at 300° C. or more and 600° C. or less to obtain the reflective electrode 80. As in this step, an inert gas such as nitrogen is generally used as the atmospheric gas used when performing a heat treatment for obtaining an ohmic contact after forming the p-side electrode. In this step, too, only an inert gas may be used as the atmospheric gas. However, in this step, it is more preferable that the atmospheric gas contains oxygen. The proportion of oxygen in the atmospheric gas is preferably more than 0% and not more than 50% in terms of flow rate ratio.
[0037] The reflective electrode 80 thus obtained is an electrode made of Ni and Rh. With the heat treatment in the third step, Ni as the first metal layer 81 diffuses from the interface in contact with the p-type contact layer 70 to the Rh side of the second metal layer 82. The diffusion of Ni increases the ratio of Rh at the interface between the p-type contact layer 70 and the reflective electrode 80, and the reflectance at the interface increases compared to before the heat treatment. In the reflective electrode 80 after the heat treatment, Ni does not maintain a layered shape but diffuses, so it is difficult to accurately measure the amount of Ni after the heat treatment (i.e., after diffusion). Therefore, if both peaks of Ni and Rh are observed in the SEM-EDS analysis of the cross section (vertical cross section) of the reflective electrode after the heat treatment, it is determined that the reflective electrode 80 made of Ni and Rh has been provided. In the reflective electrode 80, the volume ratio of Rh (corresponding to the area ratio in the mapping of the SEM-EDS analysis of the cross section of the reflective electrode) is 50% or more, and preferably 75% or more. By making the volume ratio of Rh in the reflective electrode 80 75% or more, the reflectance of the reflective electrode 80 after heat treatment for a wavelength of 300 nm can be made 60% or more. In addition, in the reflectance measurement of the reflective electrode (after the heat treatment process), the reflectance of Rh alone at a wavelength of 300 nm is 70-73%, and the reflectance of an alloy of Ni and Au is less than 40%, so that the reflectance of the reflective electrode 80 made of Ni and Rh of the present invention at a wavelength of 300 nm can be set to a range of 40% or more and less than 67% by making the thickness of the first metal layer 81 3-20 nm and the thickness of the second metal layer 82 in the range of 20 nm-2 μm, and the reflectance of the reflective electrode 80 made of Ni and Rh at a wavelength of 300 nm can be set to a range of 60% or more and less than 70% by making the thickness of the first metal layer 81 3-10 nm and the thickness of the second metal layer 82 in the range of 30 nm-100 nm. Note that even when Ni is alloyed with Rh, the reflectance of Rh alone does not decrease significantly. In addition, impurities other than Ni and Rh that may be contained in the reflective electrode 80 and do not significantly decrease the reflectance include ruthenium (Ru), gold (Au), platinum (Pt), palladium (Pd), and titanium (Ti), and the impurity content is 40 mass % or less, and preferably 10 mass % or less.
[0038] By using the reflective electrode 80 for a deep ultraviolet light emitting device according to this embodiment described above in a deep ultraviolet light emitting device, it is possible to achieve both high light emission output and excellent reliability.
[0039] Refer to FIG. 1B. As another embodiment of the above embodiment, it is also preferable to further include a step of forming a Ni layer as a third metal layer 83 on the second metal layer, and a step of forming a Rh layer as a fourth metal layer 84 on the third metal layer 83 after the second step. This step may be performed between the second step and the third step, or after the third step, but it is preferable in terms of work efficiency to perform this step between the second step and the third step and immediately after the second step. As the third metal layer 83, the Ni layer can be formed with a thickness of 1 to 20 nm. Also, as the fourth metal layer 84, the Rh layer can be formed with a thickness of 5 nm or more and 2 μm or less. Furthermore, the Ni layer and the Rh layer corresponding to the third metal layer and the fourth metal layer can be repeatedly formed on the fourth metal layer 84, and the reflective electrode can be a laminate in which the Ni layer and the Rh layer are repeatedly laminated in this order multiple times.
[0040] In a state where Au is present on the second metal layer 82, there is a risk of sudden death if Au diffuses in the reflective electrode after heating in the third step or the like, but sudden death can be suppressed by forming a reflective electrode made of Ni and Rh into a laminated structure in which the lamination order of Ni and Rh is repeated multiple times. Therefore, it is preferable to laminate Ni layers and Rh layers multiple times, since this makes it possible to more reliably avoid the risk of sudden death in an electrode without relying on a mounting process in which another metal (gold, etc.) is brought into contact with the laminated Rh layer to form an electrical connection with the outside, or a method of connection with the outside (including cases requiring heating such as soldering). From this perspective, it is particularly preferable that the metal elements constituting the reflective electrode are made of only Ni and Rh.
[0041] (Deep ultraviolet light emitting element) Next, a deep ultraviolet light emitting device 100 having a reflective electrode 80 obtained by the present invention will be described. As shown in FIG. 2, the deep ultraviolet light emitting device 100 according to one embodiment of the present invention is a deep ultraviolet light emitting device having an n-type semiconductor layer 30, a light emitting layer 40, a p-type electron blocking layer 60, a p-type contact layer 70, and the above-mentioned p-side reflective electrode 80, sequentially on a substrate 10. The reflective electrode 80 is provided on a second layer 72 on the outermost surface of the p-type contact layer. The p-type contact layer 70 is an Al layer having an Al composition ratio x. x Ga 1-x A first layer 71 made of N and an Al layer having an Al composition ratio y y Ga 1-y A superlattice structure is formed by alternately laminating a first layer 72 made of N and a second layer 73 made of N. The Al composition ratio y of the second layer 72 is 0.15 or more (y≧0.15).
[0042] In particular, when the Al composition ratio of the layer that emits deep ultraviolet light in the light emitting layer 40 is w0, the Al composition ratio x of the first layer 71 is higher than the Al composition ratio w0, the Al composition ratio y of the second layer 72 is lower than the Al composition ratio x, and the Al composition ratio w0, the Al composition ratio x, the Al composition ratio y, and the thickness-average Al composition ratio z of the p-type contact layer 70 are expressed by the following formulas [1] and [2]: 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2] It is preferable to satisfy the following:
[0043] As shown in FIG. 2, a buffer layer 20 is provided between the substrate 10 and the n-type semiconductor layer 30, a p-side reflective electrode 80 is provided directly on the p-type contact layer 70, and an n-side electrode 90 is provided on the exposed surface of the n-type semiconductor layer 30, which is a preferred embodiment of the deep ultraviolet light-emitting element 100.
[0044] In the following, for the sake of simplicity, it is assumed that the Al composition ratio and thickness of each of the first layer 71 and the second layer 72 in the superlattice structure of the p-type contact layer 70 are constant. In this case, the thickness-average Al composition ratio z of the p-type contact layer 70 is defined as follows. First, the number of layers of the first layer 71 in the superlattice structure is N, and the thickness of each layer of the first layer 71 is t a Similarly, the number of layers in the second layer 72 is represented as M, and the thickness of each layer in the second layer 72 is represented as t b In this case, the thickness-average Al composition ratio z of the p-type contact layer 70 satisfies the following formula [3].
number
[0045] It is not necessary that the Al composition ratio and thickness of each of the first layer 71 and the second layer 72 in the superlattice structure of the p-type contact layer 70 are constant. When the Al composition ratio and thickness of each of the first layer 71 and the second layer 72 in this superlattice structure vary, the thickness-average Al composition ratio z may be a weighted average value based on the thickness and Al composition ratio of each of the first layer 71 and the second layer 72, and the Al composition ratios x, y of each of the first layer 71 and the second layer 72 refer to the thickness-weighted average values.
[0046] Continuing with reference to FIG. 2, the configurations of the substrate 10, n-type semiconductor layer 30, light emitting layer 40, p-type electron blocking layer 60 and p-type contact layer 70 in the deep ultraviolet light emitting device 100 will first be described in detail.
[0047] <Substrate> As the substrate 10, it is preferable to use a substrate that can transmit the light emitted by the light-emitting layer 40. For example, a sapphire substrate or a single-crystalline AlN substrate can be used. Further, as the substrate 10, an AlN template substrate obtained by epitaxially growing an undoped AlN layer on the surface of a sapphire substrate may be used.
[0048] <n-type semiconductor layer> The n-type semiconductor layer 30 is provided on the substrate 10 via the buffer layer 20 if necessary. The n-type semiconductor layer 30 may be provided directly on the substrate 10. The n-type semiconductor layer 30 is doped with an n-type dopant. Specific examples of the n-type dopant include silicon (Si), germanium (Ge), tin (Sn), sulfur (S), oxygen (O), titanium (Ti), zirconium (Zr), etc. The dopant concentration of the n-type dopant is not particularly limited as long as it is a dopant concentration at which the n-type semiconductor layer 30 can function as an n-type. For example, 1.0×10 18 atoms / cm 3 ~1.0×10 20 atoms / cm 3 can be used. Further, the bandgap of the n-type semiconductor layer 30 is preferably wider than the bandgap of the light-emitting layer 40 (the well layer 41 in the case of a quantum well structure) and has transparency to the deep ultraviolet light emitted. In addition to a single-layer structure or a structure composed of a plurality of layers, the n-type semiconductor layer 30 can also be configured to include a compositionally graded layer or a superlattice structure in which the composition ratio of group III elements is compositionally graded in the crystal growth direction. The n-type semiconductor layer 30 not only forms a contact portion with the n-side electrode but also serves as a function of enhancing the crystallinity from the substrate to the light-emitting layer.
[0049] <Light-emitting layer> The light-emitting layer 40 is provided on the n-type semiconductor layer 30 and emits deep ultraviolet light. The light-emitting layer 40 can be made of AlGaN, and its Al composition ratio can be set so that the wavelength of the emitted light is 200 to 350 nm of deep ultraviolet light, or the central emission wavelength is 265 nm or more and 317 nm or less. Such an Al composition ratio can be, for example, in the range of 0.25 to 0.60.
[0050] The light emitting layer 40 may have a single-layer structure with a constant Al composition ratio, or may have a multiple quantum well (MQW) structure in which well layers 41 and barrier layers 42 made of AlGaN with different Al composition ratios are repeatedly formed. When the light emitting layer 40 has a single-layer structure with a constant Al composition ratio, the Al composition ratio w0 of the layer that emits deep ultraviolet light in the light emitting layer 40 is the Al composition ratio of the light emitting layer 40 itself. When the light emitting layer 40 has a multiple quantum well structure, the well layer 41 corresponds to the layer that emits deep ultraviolet light in the light emitting layer 40, and therefore, for convenience, the Al composition ratio w of the well layer 41 is treated as corresponding to the above-mentioned Al composition ratio w0. Note that the Al composition ratio w0 of the layer that emits deep ultraviolet light (or the Al composition ratio w of the well layer) is preferably set to 0.25 to 0.60 so that the wavelength of the emitted light is 200 to 350 nm of deep ultraviolet light, or the central emission wavelength is 265 nm or more and 317 nm or less.
[0051] The Al composition ratio b of the barrier layer 42 is higher than the Al composition ratio w of the well layer 41 (i.e., b>w). With respect to the Al composition ratio b, under the condition of b>w, the Al composition ratio b of the barrier layer 42 can be, for example, 0.40 to 0.95. The number of times the well layer 41 and the barrier layer 42 are repeated is not particularly limited, and can be, for example, 1 to 10 times. It is preferable that both ends (i.e., the first and the last) in the thickness direction of the light emitting layer 40 are barrier layers. If the number of times the well layer 41 and the barrier layer 42 are repeated is n, in this case, it will be expressed as "n.5 sets of well layers and barrier layers". The thickness of the well layer 41 can be 0.5 nm to 5 nm, and the thickness of the barrier layer 42 can be 3 nm to 30 nm.
[0052] <Guide layer> When the light emitting layer 40 has the above-mentioned quantum well structure, it is also preferable to provide a guide layer having an Al composition ratio higher than the Al composition ratios of both the barrier layer 42 and the p-type electron blocking layer 60 between the well layer 41 in the light emitting layer 40 that is closest to the p-type electron blocking layer 60 and the p-type electron blocking layer 60 described below. This can increase the light emission output of the deep ultraviolet light emitting device 100. In this case, the Al composition ratio of the guide layer is set to bg It is expressed as such, and if the Al composition ratio α of the p-type electron blocking layer 60 described later is used, the relationship of each Al composition ratio is as follows. w (well layer) < b (barrier layer) < α (p-type electron blocking layer) < b g (guide layer)
[0053] Also, it is preferable that the light-emitting layer 40 is composed of n sets of well layers 41 and barrier layers 42 starting from the barrier layer 42, and the layer in contact with both the light-emitting layer 40 and the p-type electron blocking layer 60 is the above-described guide layer, and its thickness is made thinner than that of other barrier layers. For example, it is also preferable that the guide layer is made of AlN (in this case, particularly referred to as an AlN guide layer), and its thickness is 0.7 to 1.7 nm.
[0054] <p-type electron blocking layer> The p-type electron blocking layer 60 is provided on the light-emitting layer 40. The p-type electron blocking layer 60 is used as a layer for blocking electrons and injecting electrons into the light-emitting layer 40 (in the case of an MQW structure, the well layer 41) to increase the electron injection efficiency. For this purpose, although it depends on the Al composition ratio w0 of the layer that emits deep ultraviolet light (in the case of a quantum well structure, corresponding to the Al composition ratio w of the well layer 41), it is preferable that the Al composition ratio α of the p-type electron blocking layer 60 satisfies 0.35 ≤ α ≤ 0.95. In addition, if the Al composition ratio α is 0.35 or more, the p-type electron blocking layer 60 may contain In in an amount within 5% with respect to Al and Ga as group III elements. Here, it is preferable that the Al composition ratio α is higher than the thickness-average Al composition ratio z of the p-type contact layer 70 while satisfying the above conditions. That is, it is preferable that α > z. Also, regarding both the Al composition ratio α of the p-type electron blocking layer 60 and the Al composition ratio b of the barrier layer 42, it is more preferable to satisfy 0 < α - b ≤ 0.55. By doing so, the electron injection efficiency into the well layer 41 by the p-type electron blocking layer 60 can be surely increased.
[0055] The thickness of the p-type electron blocking layer 60 is not particularly limited, but it is preferably, for example, 10 nm to 80 nm. If the thickness of the p-type electron blocking layer 60 is within this range, a high emission output can be surely obtained. Note that the thickness of the p-type electron blocking layer 60 is preferably greater than the thickness of the barrier layer 42. Further, examples of the p-type dopant doped into the p-type electron blocking layer 60 include magnesium (Mg), zinc (Zn), calcium (Ca), beryllium (Be), manganese (Mn), etc., and it is common to use Mg. The dopant concentration of the p-type electron blocking layer 60 is not particularly limited as long as it can function as a p-type layer, and for example, it can be 1.0×10 18 atoms / cm 3 ~5.0×10 21 atoms / cm 3 .
[0056] <p-type contact layer> The p-type contact layer 70 is provided on the p-type electron blocking layer 60. The p-type contact layer 70 is a layer for reducing the contact resistance between the p-side reflective electrode 80 provided directly above it and the p-type electron blocking layer 60. Therefore, there is no intended structure other than unavoidable impurities in manufacturing between the p-type contact layer 70 and the p-side reflective electrode 80. That is, there is a p-side reflective electrode 80 in contact with the p-type contact layer 70 having a superlattice structure.
[0057] Now, as described above, the p-type contact layer 70 has a superlattice structure formed by alternately laminating a first layer 71 made of Al x Ga 1-x N and a second layer 72 made of Al y Ga 1-y . Here, the Al composition ratio x of the first layer 71 is preferably made higher than the Al composition ratio w0 of the layer that emits deep ultraviolet light in the light-emitting layer 40 (x>w0) to increase the transmittance to deep ultraviolet light. If the light-emitting layer 40 has a single-layer structure, the Al composition ratio x may be made higher than the Al composition ratio of the light-emitting layer 40. If the light-emitting layer 40 has a quantum well structure, the Al composition ratio x may be made higher than the Al composition ratio w of the well layer 41.
[0058] As described above, the Al composition ratio w0, the Al composition ratio x, the Al composition ratio y, and the thickness-average Al composition ratio z of the p-type contact layer are expressed by the following formulas [1] and [2]: 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2] It is preferable to satisfy the following:
[0059] In the prior art, it was common to use a p-type GaN layer, which is easy to increase the hole concentration, as the p-type contact layer of a deep ultraviolet light-emitting device. However, the p-type GaN layer absorbs light with a wavelength of 360 nm or less due to its band gap. Therefore, of the deep ultraviolet light emitted from the light-emitting layer, the light extraction effect from the p-type contact layer side or the light extraction effect by reflection at the p-side electrode can hardly be expected. On the other hand, if the p-type contact layer is made of AlGaN with a high Al composition ratio, the hole concentration can be reduced to some extent compared to GaN, but the deep ultraviolet light emitted from the light-emitting layer can pass through the p-type contact layer, so that the light extraction efficiency of the deep ultraviolet light-emitting device as a whole is increased, and as a result, the light output of the deep ultraviolet light-emitting device can be increased. However, the inventors' experiments have revealed that if the Al composition ratio of the p-type contact layer is too high, the deep ultraviolet light-emitting device may have insufficient reliability. On the other hand, if the p-type contact layer 70 has a superlattice structure formed with the above-mentioned Al composition ratio, the thickness-average Al composition ratio z is higher than the Al composition ratio w0 of the layer that emits deep-ultraviolet light in the light-emitting layer 40 (z>w0), and therefore deep-ultraviolet light can pass through the p-type contact layer 70, resulting in a higher light emission output, which is preferable.
[0060] Here, in order to more reliably transmit the deep ultraviolet light through the p-type contact layer 70, it is preferable to make the difference between the thickness-average Al composition ratio z and the Al composition ratio w of the layer emitting the deep ultraviolet light higher than 0.030 (i.e., z-w0>0.030) as shown in the above formula [1]. For this purpose, it is more preferable to make the difference between the Al composition ratio z and the Al composition ratio w higher than 0.040 (z-w0>0.040), even more preferable to make it higher than 0.050 (z-w0>0.050), and particularly preferable to make it higher than 0.06 (z-w0>0.060).
[0061] Moreover, in order to obtain sufficient reliability by achieving good ohmic contact between the p-type contact layer 70 and the p-side reflecting electrode 80, it is preferable to set an upper limit on the thickness-average Al composition ratio. Thus, as shown in the above formula [1], it is preferable to set the upper limit of the difference between the thickness-average Al composition ratio z and the Al composition ratio w of the layer emitting deep ultraviolet light to 0.20 (z-w0<0.20), and for this purpose, it is more preferable to set the upper limit of the difference between the Al composition ratio z and the Al composition ratio w to 0.19 (z-w0<0.19), and further more preferable to set the upper limit to 0.18 (z-w0<0.18).
[0062] Furthermore, as shown in the above formula [2], the difference between the Al composition ratio x of the first layer 71 and the Al composition ratio y of the second layer 72 is preferably 0.050 or more (xy≧0.050) in absolute value. This is to ensure that the p-type contact layer 70 functions as a superlattice structure. In addition, in order to reduce the distortion of the entire superlattice structure and to contact the p-side reflecting electrode 80 with a low Al composition ratio, the difference between the Al composition ratio x and the Al composition ratio y is preferably 0.1 or more (xy≧0.10) in absolute value, and more preferably 0.15 or more (xy≧0.15). On the other hand, if the difference between the Al composition ratio x and the Al composition ratio y is too large, the lattice constant between the first layer and the second layer changes significantly, so that the distortion increases, and it may be difficult to obtain a superlattice layer with good crystallinity. Therefore, in order to more reliably obtain the effects of the present invention, it is preferable to set xy≦0.47, and more preferably to set xy≦0.45.
[0063] In addition, if the Al composition ratio y of the second layer 72, which is a layer with a low Al composition ratio in the superlattice structure, is 0.20 or more, the transmittance of the deep ultraviolet light from the light emitting layer 40 can be more reliably increased, which is preferable. For this purpose, it is more preferable to set the Al composition ratio y to 0.21 or more, and even more preferable to set it to 0.25 or more. On the other hand, it is preferable to set the Al composition ratio y to 0.55 or less, since high reliability can be more reliably maintained, and for this purpose, it is more preferable to set the Al composition ratio y to 0.51 or less, and particularly preferable to set it to 0.40 or less. In addition, as long as the thickness average Al composition ratio z is higher than the Al composition ratio w0 of the layer that emits deep ultraviolet light in the light emitting layer 40, the Al composition ratio y may be higher or lower than the Al composition ratio w0. In addition, the Al composition ratio x may be appropriately set as long as it satisfies the above-mentioned formulas [1] and [2], and the upper and lower limits of the Al composition ratio x are not limited. After satisfying the formulas [1] and [2], the Al composition ratio x may be set within the range of approximately 0.40 to 0.85.
[0064] The thicknesses t of the first layer 71 and the second layer 72 are a , t b is not particularly limited as long as it forms a superlattice structure and satisfies the condition of the thickness-average Al composition z relative to the Al composition ratio of the light emitting layer 40. For example, the thickness t a The thickness t of the second layer 72 can be set to 1.0 nm or more and 10.0 nm or less. b The thickness t can be set to 1.0 nm or more and 10.0 nm or less. a , t b There is no restriction on the magnitude relationship between them, and either may be larger, or the thicknesses of the two may be the same. In addition, it is preferable to appropriately set the number of repetitions of the first layer 71 and the second layer 72 within a range of, for example, 3 to 15 so that the total thickness of the p-type contact layer 70 is within a range of 20 nm to 100 nm, and preferably 70 nm or less.
[0065] The total thickness of the p-type layer, which is the sum of the thickness of the p-type electron blocking layer 60 and the thickness of the p-type contact layer 70, is preferably 65 nm to 100 nm, more preferably 70 nm to 95 nm. By keeping it within this range, a high light emission output can be obtained more reliably.
[0066] Here, it is preferable that the layer at the end of the p-type contact layer 70 closer to the p-type electron blocking layer 60 in the thickness direction of the p-type contact layer 70 is the first layer 71. In other words, when there is no other layer interposed between the p-type contact layer 70 and the p-type electron blocking layer 60 and they are in contact with each other, it is preferable that the first layer 71 is provided directly on the p-type electron blocking layer 60. The Al composition ratio x of the first layer 71 is higher than the Al composition ratio y of the second layer 72, and the Al composition ratio x is closer to the Al composition ratio α of the p-type electron blocking layer 60, so that the generation of defects due to strain between the p-type electron blocking layer 60 and the p-type contact layer 70 can be more reliably suppressed.
[0067] On the other hand, in the thickness direction of the p-type contact layer 70, the layer at the end farther from the p-type electron blocking layer 60 is preferably the second layer 72. In other words, the layer in contact with the p-side reflective electrode 80 is preferably the second layer 72. This is because, when the Al composition ratio x of the first layer 71 is compared with the Al composition ratio y of the second layer 72, the Al composition ratio y is lower, and therefore, ohmic contact with the p-side reflective electrode 80 can be easily achieved.
[0068] When the layer at the end of the p-type contact layer 70 in the thickness direction closer to the p-type electron blocking layer 60 is the first layer 71 and the layer at the end farther from the p-type electron blocking layer 60 is the second layer 72, the number of first layers 71 and the number of second layers 72 will be the same. However, in this embodiment, the numbers of both layers do not necessarily need to be the same. This embodiment also includes the case where both layers at the ends of the p-type contact layer 70 in the thickness direction are the second layers 72 (in this case, the number of second layers 72 is one more than the number of first layers 71).
[0069] Although a superlattice structure in which two layers, the first layer 71 and the second layer 72, are repeatedly laminated has been described as one embodiment according to the present invention, another embodiment according to the present invention may be applied in which a three-layer superlattice structure is applied in which a third layer having an Al composition ratio between the first and second layers is disposed between the first and second layers while maintaining the same relationship between the first and second layers. In this case, the same effect as that of the present invention described above can be obtained.
[0070] Here, the p-type contact layer 70 has an Mg concentration of 3×10 20 atoms / cm 3 It is preferable that the Mg concentration in the high concentration region is 5×10 20 atoms / cm 3 More preferably, the hole concentration in the p-type contact layer 70 is increased, thereby decreasing the forward voltage Vf of the deep ultraviolet light emitting device 100. Although no upper limit is intended, in this embodiment, the upper limit of the Mg concentration in the high concentration region is set to 1×10 21 atoms / cm 3 In this case, the Mg concentration in the region of the p-type contact layer 70 on the p-type electron blocking layer 60 side can be in a general range, typically 5×10 19 atoms / cm 3 More than 3×10 20 atoms / cm 3 The Mg concentration in the p-type contact layer is the average concentration in each region measured by SIMS. In order to maintain the crystallinity of the p-type contact layer 70, the thickness of the high-concentration region is usually 15 nm or less, and several layers on the side in contact with the p-side reflective electrode 80 can be made into the high-concentration region.
[0071] Furthermore, the p-type contact layer 70 has a Si concentration of 5×10 16 atoms / cm 3 More than 1×10 20 atoms / cm 3It is also preferable to have a Si-doped region in which the Si concentration is 2×10 19 atoms / cm 3 5×10 or more 19 atoms / cm 3 It is more preferable that the thickness of the Si-doped region is 1 to 5 nm or less. This makes it possible to further increase the light emission output of the deep ultraviolet light emitting element 100. This effect can be reliably obtained if the thickness of the Si-doped region is about 1 to 5 nm. It is also preferable that the Si-doped region is the last second layer in the superlattice structure of the p-type contact layer. 20 atoms / cm 3 The high concentration region may be further doped with Si to form a co-doped region, or the Si-doped region may be doped with only Si (i.e., Mg may not be doped).
[0072] In addition, when a Si-doped region in which only Si is doped is provided on the side of the p-type contact layer 70 in contact with the p-side reflective electrode 80, but is not doped with Mg, the region can be considered to be of n-type conductivity. However, in the above thickness range (1 to 5 nm), even if it is not doped with Mg, it will not become a thyristor if it is in contact with the p-type electrode as the uppermost layer of the p-type contact layer 70. Therefore, even in such a case, the Si-doped region is considered to be part of the p-type contact layer 70.
[0073] The deep ultraviolet light emitting device 100 according to this embodiment described above can achieve both high light emission output and excellent reliability.
[0074] Specific embodiments applicable to the deep ultraviolet light emitting device 100 of this embodiment will be described below, but this embodiment is not limited to the following embodiments.
[0075] <Buffer layer> As shown in FIG. 2, it is also preferable to provide a buffer layer 20 for relaxing the lattice mismatch between the substrate 10 and the n-type semiconductor layer 30. An undoped group-III nitride semiconductor layer can be used as the buffer layer 20, and it is also preferable that the buffer layer 20 has a superlattice structure.
[0076] <n-side electrode> In addition, the n-side electrode 90 that can be provided on the exposed surface of the n-type semiconductor layer 30 can be, for example, a metal composite film having a Ti-containing film and an Al-containing film formed on this Ti-containing film. The thickness, shape, and size of the n-side electrode 90 can be appropriately selected according to the shape and size of the light-emitting element. The n-side electrode 90 is not limited to being formed on the exposed surface of the n-type semiconductor layer 30 as shown in FIG. 2, and it only needs to be electrically connected to the n-type semiconductor layer.
[0077] <Other configurations> Although not shown in FIG. 2, a guide layer made of AlGaN having an Al composition ratio higher than the Al composition ratio α of the p-type electron blocking layer 60 may be provided between the light-emitting layer 40 and the p-type electron blocking layer 60. By providing the guide layer, the injection of holes into the light-emitting layer 40 can be promoted.
[0078] <p-type cladding layer> Although not shown in FIG. 2, a p-type cladding layer made of AlGaN may be provided between the p-type electron block layer 60 and the p-type contact layer 70. The p-type cladding layer is a layer having an Al composition ratio higher than the Al composition ratio (Al composition ratio w in the case of a quantum well structure) of the layer that emits deep ultraviolet light in the light-emitting layer 40 and the thickness average Al composition ratio z of the p-type contact layer 70, while being lower than the Al composition ratio α of the p-type electron block layer 60. In other words, both the p-type electron block layer 60 and the p-type cladding layer are layers having an Al composition ratio higher than the Al composition ratio of the layer that emits deep ultraviolet light, and are layers that substantially transmit the deep ultraviolet light emitted from the light-emitting layer 40. However, it is preferable not to provide a p-type cladding layer. The reason for this is as described in JP 2016-111370 A, the entire disclosure of which is incorporated herein by reference. When a p-type cladding layer is provided, if the Al composition ratio of the p-type cladding layer is β, then α>β and β>y.
[0079] In addition, in the deep ultraviolet light emitting device 100 according to this embodiment, the p-side reflective electrode 80 is formed from a reflective electrode material to reflect deep ultraviolet light, so that the main light extraction direction is the substrate side or the substrate horizontal direction. Also, the deep ultraviolet light emitting device 100 can be in a form called a flip chip type.
[0080] (Method of manufacturing deep ultraviolet light emitting device) Next, one embodiment for obtaining a manufacturing method of the above-mentioned deep ultraviolet light emitting device 100 will be described with reference to Fig. 3. One embodiment of the manufacturing method of the deep ultraviolet light emitting device 100 according to the present invention includes a step of forming an n-type semiconductor layer 30 on a substrate 10 (see Fig. 3, step 3A), a step of forming a light emitting layer 40 on the n-type semiconductor layer 30, a step of forming a p-type electron blocking layer 60 on the light emitting layer 40 (see Fig. 3, step 3B), a step of forming a p-type contact layer on the p-type electron blocking layer (see Fig. 3, step 3C), and a step of forming a reflective electrode on the p-type contact layer (see Fig. 3, step 3D). The step of forming the p-type contact layer includes forming an Al x Ga 1-xA first step of forming a first layer made of N and a second step of forming an Al layer having an Al composition ratio y lower than the Al composition ratio x. y Ga 1-y The p-type contact layer 70 is formed by alternately repeating the steps of forming a first metal layer 81 of Ni with a thickness of 3 to 20 nm on the p-type contact layer 70 having a superlattice structure, and the second layer has an Al composition ratio y of 0.15 or more. As described in the embodiment of the reflective electrode 80, the step of forming the reflective electrode includes a first step of forming a first metal layer 81 of Ni with a thickness of 3 to 20 nm on the p-type contact layer 70 having a superlattice structure, a second step of forming a second metal layer 82 of Rh with a thickness of 20 nm or more and 2 μm or less on the first metal layer 81, and a third step of performing a heat treatment at 300° C. or more and 600° C. or less on the first metal layer and the second metal layer (see FIG. 1A). The step of forming the p-type contact layer 70 (see step 3C) includes a step of forming a first metal layer 81 of Ni with an Al composition ratio x with a thickness of 3 to 20 nm on the p-type contact layer 70 having a superlattice structure, a second step of forming a second metal layer 82 of Rh with a thickness of 20 nm or more and 2 μm or less on the first metal layer 81, and a third step of performing a heat treatment at 300° C. or more and 600° C. or less on the first metal layer and the second metal layer (see FIG. 1A). x Ga 1-x A first step of forming a first layer 71 made of N and a second step of forming an Al layer having an Al composition ratio y lower than an Al composition ratio x. y Ga 1-y A second step of forming a second layer 72 made of N is alternately repeated to form a p-type contact layer 70 having a superlattice structure, and the Al composition ratio y of the second layer 72 is 0.15 or more (y≧0.15).
[0081] Furthermore, when the Al composition ratio of the layer that emits deep ultraviolet light in the light emitting layer 40 is w0, the Al composition ratio x of the first layer 71 is higher than the Al composition ratio w0, the Al composition ratio y of the second layer 72 is lower than the Al composition ratio x, and the Al composition ratio w0, the Al composition ratio x, the Al composition ratio y, and the thickness-average Al composition ratio z of the p-type contact layer 70 are expressed by the following formulas [1] and [2]: 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2] It is preferable to satisfy the following:
[0082] The description will continue with reference to the flowchart in Fig. 3. However, the description overlapping with the above embodiment will be omitted.
[0083] 3, n-type semiconductor layer 30, light-emitting layer 40, and p-type electron blocking layer 60 are sequentially formed on substrate 10. In each of these steps, each layer can be formed by a known epitaxial growth technique such as metal organic chemical vapor deposition (MOCVD), molecular beam epitaxy (MBE), or sputtering.
[0084] In forming each of the n-type semiconductor layer 30, the light emitting layer 40, the guide layer, and the p-type electron blocking layer 60, the growth temperature, growth pressure, and growth time for epitaxial growth can be general conditions according to the Al composition ratio and thickness of each layer. As a carrier gas for epitaxial growth, hydrogen gas, nitrogen gas, or a mixture of both can be used and supplied into the chamber. Furthermore, as a raw material gas for growing each of the above layers, TMA (trimethylaluminum), TMG (trimethylgallium), etc. can be used as a raw material gas for III elements, and NH3 gas can be used as a group V element gas. The molar ratio of the V element to the III element (hereinafter referred to as V / III ratio) calculated based on the growth gas flow rate of the V element gas such as NH3 gas and the III element gas such as TMA gas can also be general conditions. Furthermore, as the dopant source gas, for a p-type dopant, cyclopentadienyl magnesium gas (CP2Mg) or the like is used as the Mg source, and for an n-type dopant, for example, monosilane gas (SiH4) is used as the Si source, zinc chloride gas (ZnCl2) is used as the Zn source, etc. are appropriately selected and supplied into the chamber at a predetermined flow rate.
[0085] 3, a p-type contact layer 70 having a superlattice structure in which the above-mentioned first layer 71 and second layer 72 are repeated is formed on the p-type electron block layer 60. The thickness range and Al composition ratio conditions of the p-type contact layer 70 are as described above. The p-type contact layer 70 may also be grown as a crystal by epitaxial growth using the MOCVD method or the like.
[0086] In the p-type contact layer 70, the Mg concentration of the high concentration region 72 on the side in contact with the p-side reflecting electrode 80 is set to 3×10 20 atoms / cm 3 To achieve the above, the following process may be performed in the p-type contact layer formation step: In other words, in the p-type contact layer formation step, a Group III source gas, a Group V source gas, and an Mg source gas are supplied to grow the above-mentioned superlattice structure, and immediately after the end of the crystal growth, the flow rate of the Group III source gas is reduced to ¼ or less of the flow rate during crystal growth, while the Group V source gas and the Mg source gas are continuously supplied for 1 minute to 20 minutes.
[0087] To dope both Mg and Si on the side of the p-type contact layer 70 that contacts the p-side reflective electrode 80, CP2Mg gas may be supplied to the chamber as the Mg source and monosilane gas (SiH4) or the like may be supplied as the Si source. To dope only Si, the supply of CP2Mg gas as the Mg source to the chamber may be stopped and monosilane gas (SiH4) may be supplied as the Si source. When doping Si on the side of the p-type contact layer 70 that contacts the p-side reflective electrode 80 as described above, the formation of the high concentration region of Mg described above is optional.
[0088] 3, the light-emitting layer 40, the p-type electron blocking layer 60, and the p-type contact layer 70 may be partially removed by etching or the like, and an n-side electrode 90 may be formed on the exposed n-type semiconductor layer 30. The n-side electrode 90 may be formed by sputtering, vacuum deposition, or the like. It is also preferable to form the buffer layer 20 on the surface 10A of the substrate 10. EXAMPLES
[0089] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples in any way.
[0090] Example 1 According to the process diagrams shown in FIG. 1A and FIG. 3, a deep ultraviolet light emitting device according to Example 1 was fabricated. First, a sapphire substrate (diameter 2 inches, thickness: 430 μm, surface orientation: (0001)) was prepared. Next, an AlN layer having a central thickness of 0.60 μm was grown on the sapphire substrate by MOCVD to prepare an AlN template substrate. At this time, the growth temperature of the AlN layer was 1300° C., the growth pressure in the chamber was 10 Torr, and the growth gas flow rates of ammonia gas and TMA gas were set so that the V / III ratio was 163. The thickness of the AlN layer was measured at a total of 25 points distributed at equal intervals, including the center of the wafer, using an optical interference film thickness measuring device (Nanospec M6100A; manufactured by Nanometrics).
[0091] Next, the AlN template substrate was introduced into a heat treatment furnace, and after the inside of the furnace was filled with nitrogen gas, the temperature inside the furnace was raised to perform a heat treatment on the AlN template substrate at a heating temperature of 1650° C. for a heating time of 4 hours.
[0092] Next, undoped Al was grown by MOCVD. 0.55 Ga 0.45 A 1 μm thick buffer layer of AlN was then formed. 0.45 Ga 0.55 A 2 μm-thick n-type semiconductor layer made of N and doped with Si was formed on the buffer layer. The results of SIMS analysis showed that the Si concentration in the n-type semiconductor layer was 1.0×10 19 atoms / cm 3 It was.
[0093] Furthermore, on the n-type semiconductor layer, Al 0.29 Ga 0.71 A 3-nm-thick well layer of N and Al 0.51 Ga 0.49 The light-emitting layer was formed by alternately stacking three sets of 7 nm-thick barrier layers made of AlN. The Al composition ratio w of the well layer was 0.29. Next, a 1 nm-thick guide layer made of AlN was formed on the light-emitting layer. The barrier layers were doped with Si, while the well layers and guide layers were undoped.
[0094] Then, Al was deposited on the guide layer using hydrogen gas as a carrier gas. 0.58 Ga 0.42 A p-type electron blocking layer of 40 nm thickness was formed and made of N. In forming the p-type electron blocking layer, CP2Mg gas was supplied to the chamber as a Mg source to dope Mg. As a result of SIMS analysis, the Mg concentration in the p-type electron blocking layer was 5.0×10 18 atoms / cm 3 It was.
[0095] Next, an Al layer is formed on the p-type electron blocking layer as the first layer. 0.47 Ga 0.53 N is formed, and then Al is formed as the second layer. 0.31 Ga 0.69 N was formed, and the formation of both was repeated 7 times to form a p-type contact layer with a superlattice structure of 14 layers in total. The thickness of the first layer was 5.0 nm, the thickness of the second layer was 2.5 nm, and the total thickness of the p-type contact layer was 52.5 nm, with the average Al composition of the thickness being 0.42. In addition, in forming the p-type contact layer, CP2Mg gas was supplied as an Mg source together with TMA gas and TMG gas, which are group III sources, and ammonia gas, which is group V source, to the chamber to grow a Mg-doped p-type contact layer. After that, the supply of only the group III source gas was stopped, and only the Mg source gas and the group V source gas were supplied for 10.5 minutes to form a high concentration region on the surface side of the p-type contact layer.
[0096] In addition, when specifying the Al composition of the p-type contact layer, the Al composition ratio of the p-type contact layer was determined from the emission wavelength (band gap energy) of the p-type contact layer analyzed by photoluminescence measurement.
[0097] SIMS analysis revealed that the Mg concentration on the p-type electron blocking layer side of the p-type contact layer was 1×10 20 atoms / cm 3 The Mg concentration in the high-concentration region on the surface side forming the p-side reflecting electrode 80 opposite to the p-type electron blocking layer is 3×10 20 atom / cm3 It was.
[0098] The layer structure of Example 1 is shown in Table 1.
[0099] [Table 1]
[0100] A mask was formed on the p-type contact layer and mesa etching was performed by dry etching to expose the n-type semiconductor layer. Next, the second layer (Al 0.31 Ga 0.69 A 7 nm thick Ni layer (first metal layer) and a 50 nm thick Rh layer (second metal layer) were formed on the Ni layer by electron beam deposition on a quartz crystal oscillator. The thicknesses of the Ni layer and the Rh layer were measured using a quartz crystal oscillator thickness gauge (CRTM-9000G; manufactured by Ulvac). The oscillator was gold plated and had a natural frequency of 4.5 MHz to 5.0 MHz. The calibration curve (calibration) of the quartz crystal oscillator was performed by depositing a single film of the target metal with a thickness of 100 nm or more, and measuring the step between the film and no film using a stylus step gauge (P-6; manufactured by Tencor). In addition, an n-side electrode made of Ti / Al was formed on the exposed n-type semiconductor layer. The Ti thickness was 20 nm, and the Al thickness was 150 nm. Finally, a heat treatment for ohmic contact was performed by holding the maximum temperature of 550°C for 10 minutes using an RTA device (manufactured by Advance Riko; infrared lamp annealing heating device), and a reflective electrode made of Ni and Rh was formed. The heat treatment atmosphere in the RTA device was a mixed gas of N2 and O2, with the N2 flow rate in the mixed gas being 1.0 slm and the O2 flow rate being 0.5 slm. The sapphire substrate was laser scribed to be divided into chips with a size of 1000 μm × 1000 μm, and a deep ultraviolet light emitting device according to Example 1 was fabricated.
[0101] A 7 nm thick Ni layer (first metal layer) and a 50 nm thick Rh layer (second metal layer) were formed on a sapphire substrate, and after the above-mentioned heat treatment process, the reflectance against wavelength was measured from the transparent sapphire substrate side toward the reflective electrode using an ultraviolet-visible spectrophotometer (JASCO Corporation; V-650). The reflectance against a wavelength of 300 nm was 62%.
[0102] Example 2 A deep ultraviolet light-emitting device according to Example 2 was fabricated and evaluated in the same manner as in Example 1, except that the heat treatment atmosphere in the RTA apparatus was changed to N2 gas (N2 flow rate 1.5 slm) instead of the mixed gas atmosphere in Example 1.
[0103] Example 3 A deep ultraviolet light emitting device according to Example 3 was fabricated and evaluated in the same manner as in Example 1, except that the Al composition ratio x of the first layer was set to 0.43 and the Al composition ratio y of the second layer was set to 0.27.
[0104] Comparative Example 1 A deep ultraviolet light emitting device according to Comparative Example 1 was fabricated and evaluated in the same manner as in Example 1, except that the thickness of the Ni reflective electrode in Example 1 was changed to 2 nm.
[0105] A 2 nm thick Ni layer (first metal layer) and a 50 nm thick Rh layer (second metal layer) were formed on a sapphire substrate, and after the above-mentioned heat treatment process, the reflectance against wavelength was measured from the transparent sapphire substrate side toward the reflective electrode using an ultraviolet-visible spectrophotometer (JASCO Corporation; V-650). The reflectance against a wavelength of 300 nm was 67%.
[0106] Comparative Example 2 A deep ultraviolet light emitting device according to Comparative Example 2 was produced and evaluated in the same manner as in Example 1, except that the Ni reflective electrode in Example 1 was not provided.
[0107] Comparative Example 3 The p-type contact layer (total thickness 52.5 nm) of the superlattice structure in Example 1 was formed of Al 0.42 Ga 0.58A deep ultraviolet light emitting device according to Comparative Example 3 was produced and evaluated in the same manner as in Example 1, except that the N layer was changed to a single layer structure with a thickness of 50 nm.
[0108] Comparative Example 4 A deep ultraviolet light-emitting device according to Comparative Example 4 was fabricated in the same manner as in Example 1, except that the reflective electrode made of Ni and Rh in Example 1 was changed to one having a Ni layer having a thickness of 10 nm and a Au layer having a thickness of 20 nm formed on the Ni layer in that order, and the light emission output was evaluated.
[0109] Comparative Example 5 The reflective electrode made of Ni and Rh in Example 1 was changed to one having a Ni layer having a thickness of 10 nm and a Au layer having a thickness of 20 nm formed on the Ni layer in that order, and the Al composition ratio x of the first layer was set to 0.43, and the Al composition ratio y of the second layer was set to 0.27. Except for this, the light emission output of the deep ultraviolet light-emitting device according to Comparative Example 5 was evaluated in the same manner as in Example 1.
[0110] (Comparative Examples 11 to 13) The p-type contact layer of the superlattice structure in Example 1 was replaced with a single-layer structure of an AlGaN layer, the Al composition ratio and thickness of which were as shown in Table 3, and Ni was not used for the reflective electrode. In addition, deep ultraviolet light-emitting devices according to Comparative Examples 11 to 13 were fabricated and evaluated in the same manner as in Example 1, except that the chip size was 560 μm×780 μm.
[0111] (Rating 1: Po, Vf rating) The light-emitting elements (chip size 1000 μm) obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were mounted on an AlN submount (size 20 mm × 15 mm, thickness 0.8 mm) using spherical Au bumps by flip-chip method. Furthermore, with an Al heat sink connected to the AlN submount, a current of 350 mA was applied using a constant current power supply, and the forward voltage at that time was measured, and the light output was measured by a photodetector using a light receiving unit arranged on the sapphire substrate side. The results are shown in Table 2. The emission wavelength was measured using a spectrum analyzer, and the emission center wavelength was 310 nm for all of them. The value is the average value of 10 measurements.
[0112] (Rating 2: Reliability Rating 1) After carrying out the measurement of the above-mentioned evaluation 1 for the examples and comparative examples 1 to 5, 350 mA was continuously applied for 160 hours. After the continuous application of electricity, the output was measured again and compared with the initial output, and it was determined that sudden death had occurred if the light did not light up or the output suddenly decreased to less than half of the initial light output. The ratio of sudden death among the 10 chips measured is shown in Table 2.
[0113] (Rating 3: Reliability Rating 2) For Comparative Examples 11 to 13, a mask was formed on the p-type contact layer, mesa etching was performed by dry etching, and the n-type semiconductor layer was exposed. A small chip with a size of 560 μm×780 μm was mounted on an AlN submount (size: 1.5×1.1 mm, thickness: 0.2 mm) using Au bumps on the exposed n-type semiconductor layer and p-type contact layer, and the light emission output and forward current thickness when 20 mA was applied were measured. The values are the average values of 10 pieces. Furthermore, for chips taken out from 10 places in the wafer, a current of 20 mA was applied to check the initial light emission output, and then a current of 20 mA was applied continuously for 250 hours. The ratio of chips whose output was reduced by half or less from the initial light emission output after application of the current (i.e., died suddenly) is shown in Table 3. In addition, a photodetector arranged on the sapphire substrate side was used for measuring the light emission output. [Table 2]
[0114] [Table 3]
[0115] Since the thickness of the first layer is 5.0 nm and the thickness of the second layer is 2.5 nm, the thickness-average Al composition ratio z of the p-type contact layer is calculated as [z=(2 / 3)x+(1 / 3)y]. In Examples 1 and 2, z-w0=0.42-0.29=0.13, and xy=0.47-0.31=0.16. Therefore, the following conditions [1] and [2] are simultaneously satisfied. 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2]
[0116] (Discussion of evaluation results) The sudden deaths in Comparative Examples 1 to 3 are believed to be due to contact failures at the interface between the p-type contact layer and the p-side reflective electrode. On the other hand, in Examples 1 to 3, it is presumed that no contact failures occurred because the p-type contact layer has a superlattice structure and the Ni layer has a sufficient thickness. In addition, a comparison of Comparative Examples 4 and 5 with Examples 1 to 3 shows that a reflective electrode made of Ni and Rh is effective in increasing the light output without significantly changing the forward voltage.
[0117] From the above results, it was confirmed that by forming a p-side reflective electrode that satisfies the conditions of the present invention on a p-type contact layer with a superlattice structure, it is possible to obtain high light emission output while also achieving high reliability.
[0118] Example 4 In Examples 1 to 3, the central emission wavelength was 310 nm, but instead, an experiment was performed using a deep ultraviolet light-emitting device with a central emission wavelength of 280 nm. A deep ultraviolet light-emitting device according to Example 4 was fabricated in the same manner as in Example 1, except that the Al composition ratio of each semiconductor layer in Example 1 was changed as shown in Table 4 below. The undoped AlGaN layer on the AlN template substrate was formed by grading the composition in the crystal growth direction from an Al composition ratio of 0.85 to 0.65.
[0119] [Table 4]
[0120] Comparative Example 6 A deep ultraviolet light-emitting device according to Comparative Example 6 was fabricated in the same manner as in Example 4, except that the reflective electrode made of Ni and Rh in Example 4 was changed to one having a Ni layer having a thickness of 10 nm and a Au layer having a thickness of 20 nm formed on the Ni layer in that order, and the light emission output was evaluated.
[0121] Comparative Example 7 The p-type contact layer (total thickness 52.5 nm) of the superlattice structure in Example 4 was made of Al 0.59 Ga 0.41 A deep ultraviolet light emitting device according to Comparative Example 3 was produced and evaluated in the same manner as in Example 1, except that the N layer was changed to a single layer structure with a thickness of 50 nm.
[0122] (Rating 4) For Example 4 and Comparative Examples 6 and 7 (all chip sizes 1000 μm×1000 μm, like Example 1), the light output Po and forward voltage Vf were measured and evaluated in the same manner as in Evaluation 1 described above. The results are shown in Table 5. Next, after this measurement, 350 mA was continuously applied for 20 hours. After the continuous application of current, the output was measured again and compared with the initial output. If the output did not light up or there was a sudden drop in output to less than half of the initial light output, it was determined that sudden death had occurred. The ratio of chips that died suddenly out of the 10 measured chips is also shown in Table 5.
[0123] [Table 5]
[0124] In the fourth embodiment, z-w0=0.59-0.45=0.14, and xy=0.71-0.35=0.36. Therefore, the following conditions [1] and [2] are simultaneously satisfied. 0.030 <z-w0<0.20 ···[1] 0.050≦xy≦0.47 [2]
[0125] (Discussion of evaluation results) The sudden death in Comparative Example 7 is believed to be due to contact failure at the interface between the p-type contact layer and the p-side reflective electrode, as in Comparative Example 3. On the other hand, in Example 4, it is presumed that no contact failure occurred because the p-type contact layer has a superlattice structure and the Ni layer has a sufficient thickness. In addition, when Example 4 is compared with Comparative Example 6, it is found that the reflective electrode made of Ni and Rh is effective in increasing the light output without significantly changing the forward voltage.
[0126] Example 5 Each semiconductor layer was formed in the same manner as in Example 4, and then a 7 nm thick Ni layer (first metal layer) and a 50 nm thick Rh layer (second metal layer) were formed in sequence on the Ni layer by using an electron beam deposition method. Subsequently, a 3 nm thick Ni layer was formed as a third metal layer on the Rh layer (second metal layer), and then a 20 nm thick Rh layer was formed in sequence as a fourth metal layer. Thereafter, a heat treatment for ohmic contact was performed in the same manner as in Example 4. The other manufacturing conditions were the same as in Example 4. In this way, a deep ultraviolet light emitting device according to Example 5 was manufactured. The total thickness of the p-type layers of the p-type electron block layer and the p-type contact layer was 92.5 nm.
[0127] Comparative Example 8 In Example 5, a 3 nm thick Ni layer was formed as a third metal layer on the Rh layer (second metal layer), and then a 20 nm thick Rh layer was formed in that order as a fourth metal layer. A deep ultraviolet light-emitting device according to Comparative Example 8 was produced in the same manner as in Example 5, except that a 20 nm thick Au layer was formed on the Rh layer (second metal layer).
[0128] Comparative Example 9 In Example 5, a 3 nm thick Ni layer was formed as the third metal layer on the Rh layer (second metal layer), and then a 20 nm thick Rh layer was formed in that order as the fourth metal layer.A deep ultraviolet light-emitting device of Comparative Example 9 was produced in the same manner as Example 5, except that a 3 nm thick Ni layer was formed as the third metal layer on the Rh layer (second metal layer), and then a 20 nm thick Au layer was formed as the fourth metal layer.
[0129] (Rating 5) In Evaluation 4, the continuous current application time was set to 20 hours, but this was extended to 168 hours and 1000 hours, and the same procedure as in Evaluation 4 was repeated to confirm the presence or absence of sudden death in the above Examples and Comparative Examples. The evaluation results in Evaluation 5 are shown in Table 6.
[0130] [Table 6]
[0131] From Table 6, it was found that even if the occurrence of sudden death is suppressed by combining the p-type contact layer with the superlattice structure according to the present invention with the reflective electrode of Ni and Rh, in a state where Au is present on the Rh layer (second metal layer), there is a risk of sudden death occurring if Au diffuses in the reflective electrode after heating in the third step, etc. It was also found that the rate of sudden death occurrence can be suppressed for a long period of time by forming the reflective electrode of Ni and Rh into a laminated structure in which the layer order of Ni and Rh is repeated multiple times.
[0132] Example 6 Except for changing the thickness of the p-type electron blocking layer from 40 nm to 33 nm, a deep ultraviolet light-emitting device according to Example 6 was fabricated and evaluated in the same manner as in Example 5. The total thickness of the p-type electron blocking layer and the p-type layer of the p-type contact layer was 85.5 nm.
[0133] Example 7 Except for reducing the thickness of the first layer of the p-type contact layer from 5 nm to 2.5 nm and setting the thickness-average Al composition ratio z to 0.53, the deep ultraviolet light-emitting device of Example 7 was fabricated and evaluated in the same manner as in Example 5. The total thickness of the p-type of the p-blocking layer and the p-type contact layer was 75 nm.
[0134] For Examples 6 and 7, the presence or absence of sudden death was confirmed in the same manner as in Evaluation 5. The preparation conditions and evaluation results of Examples 6 and 7 are shown in Table 7 below, together with those of Example 5 and Comparative Example 6 described above for comparison.
[0135] [Table 7]
[0136] From Table 7, it was found that the light emission output can be further improved by adjusting the sum of the thickness of the p-type electron blocking layer 60 and the thickness of the p-type contact layer 70 (total thickness of the p-type layers). The total thickness of the p-type layers is preferably 65 nm or more and 100 nm or less, and more preferably 70 nm or more and 95 nm or less. Furthermore, an electrode with higher light emission output and higher reliability than an electrode using Ni and Au was obtained. [Industrial Applicability]
[0137] According to the present invention, it is possible to provide a method for producing a reflective electrode for a deep ultraviolet light-emitting device that can achieve both high light emission output and excellent reliability. Furthermore, the present invention can provide a method for producing a deep ultraviolet light-emitting device using the reflective electrode, and a deep ultraviolet light-emitting device obtained thereby. [Explanation of symbols]
[0138] 10 Substrate 20 Buffer Layer 30 n-type semiconductor layer 40 Light-emitting layer 41 Well Layer 42 Barrier Layer 60 p-type electron blocking layer 70 p-type contact layer 71 1st layer 72 2nd layer 80 reflective electrode 81 1st metal layer 82 Second metal layer 83 Third metal layer 84 4th metal layer 90 n-side electrode 100 Deep ultraviolet light emitting device
Claims
1. On a p-type contact layer having a superlattice structure, A first step of forming a first metal layer of Ni to a thickness of 3 to 10 nm; a second step of forming a second metal layer of Rh on the first metal layer to a thickness of 30 nm or more and 100 nm or less; a third step of subjecting the first metal layer and the second metal layer to a heat treatment at 300° C. or more and 600° C. or less, the heat treatment being performed using an atmospheric gas containing oxygen; A method for manufacturing a reflective electrode for a deep ultraviolet light-emitting element, comprising:
2. 2. The method for producing a reflective electrode for a deep ultraviolet light-emitting element according to claim 1, further comprising the step of forming a Ni layer as a third metal layer on the second metal layer after the second step, and the reflective electrode is formed only from Ni and Rh.
3. forming an n-type semiconductor layer on a substrate; forming a light emitting layer on the n-type semiconductor layer; forming a p-type electron blocking layer on the light emitting layer; forming a p-type contact layer on the p-type electron blocking layer; forming a reflective electrode on the p-type contact layer; A method for producing a deep ultraviolet light emitting device comprising: The step of forming the p-type contact layer includes forming an Al x G 1-x A first step of forming a first layer made of N; and a second step of forming an Al layer having an Al composition ratio y lower than the Al composition ratio x. y G 1-y and a second step of forming a second layer made of N. These steps are alternately repeated to form the p-type contact layer having a superlattice structure, and the Al composition ratio y of the second layer is 0.15 or more, The step of forming a reflective electrode includes: on the second layer on the outermost surface of the p-type contact layer, A first step of forming a first metal layer of Ni to a thickness of 3 to 10 nm; a second step of forming a second metal layer of Rh on the first metal layer to a thickness of 30 nm or more and 100 nm or less; a third step of subjecting the first metal layer and the second metal layer to a heat treatment at 300 to 600° C., the heat treatment being performed using an atmospheric gas containing oxygen; A method for manufacturing a deep ultraviolet light-emitting device, comprising:
4. In the superlattice structure of the p-type contact layer, The Al composition ratio of the layer that emits deep ultraviolet light in the light emitting layer is w 0 When The Al composition ratio x of the first layer is the Al composition ratio w 0 Higher than the Al composition ratio y of the second layer is lower than the Al composition ratio x of the second layer, The Al composition ratio w0, the Al composition ratio x, the Al composition ratio y, and the thickness-average Al composition ratio z of the p-type contact layer are expressed by the following formulas [1] and [2]: 0.030<z-w 0 <0.20 ・・・[1] 0.050≦x−y≦0.47... [2] The method for producing a deep ultraviolet light-emitting device according to claim 3 , which satisfies the above.
5. 5. The method for producing a deep ultraviolet light-emitting element according to claim 4, further comprising: a guide layer between the p-type electron blocking layer and a well layer in the light-emitting layer that is closest to the p-type electron blocking layer, the guide layer having an Al composition ratio higher than an Al composition ratio of either of the barrier layer of the light-emitting layer and the p-type electron blocking layer.
6. The method for producing a deep ultraviolet light emitting device according to claim 5 , wherein the guide layer is made of AlN.
7. The method for manufacturing a deep ultraviolet light-emitting device according to any one of claims 4 to 6, wherein the Al composition ratio w0 is 0.25 or more and 0.60 or less.
8. The method for producing a deep ultraviolet light-emitting device according to any one of claims 3 to 7, wherein a total thickness of the p-type layers, that is, the p-type electron blocking layer and the p-type contact layer, is 65 to 100 nm.
9. The method for producing a deep ultraviolet light-emitting element according to any one of claims 3 to 8, further comprising the step of forming a Ni layer as a third metal layer on the second metal layer after the second step, and forming the reflective electrode only from Ni and Rh.
Citation Information
Patent Citations
High reflectivity LED electrode and preparing method thereof
CN106328781A
Iii nitride compound semiconductor light emitting element
JP2000036619A
Ultraviolet light emitting diode
JP2002280610A
Light emitting diode
JP2004281553A
Semiconductor light-emitting element, and semiconductor light-emitting device
JP2012182211A